Collodion Baby: Non Bullous Ichthyosiform Erythroderma - A case Report - Khan, Inam Ullah; Hakim, Irshad; Khan, Mairaj Muhammad (Journal of Postgraduate Medical Institute, 2011)
Collodion baby is a condition in which infants are bon with a distinctive, tough inelastic collodion like membrane covering their bodies. The membrane eventually fissures and and is shed, usually revealing a characteristic Ichthyosiform abnormality.